Setting the course after elections in Indonesia: President Prabowo Subianto and the complex legacy of Jokowi - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2024)
In mid-February, the world's largest elections took place in Indonesia over the course of a single day. Around 205 million eligible voters were called to the polls to elect a new president, vice president and almost 20,000 representatives for the national, provincial and district parliaments. The spotlight was largely centred on the presidential election, as the president plays a prominent role in the country's political system, and according to the official results released on 20 March, General Prabowo Subianto will be assuming office in October. His election as head of state is seen by some observers as a threat to Indonesian democracy or even a return to dictatorship. However, it is much more likely that Prabowo will maintain the policies of his predecessor Jokowi, who prioritised the economic development of the country. Nonetheless, democratic institutions and procedures are likely to be further weakened. Germany and the EU should be prepared for Indonesia to adopt a more active and self-confident foreign policy stance under Prabowo as Jakarta will likely come to be driven by a decidedly transactional understanding of international cooperation.
Keywords: 320; Indonesia; elections; General Prabowo Subianto; Joko Widodo ("Jokowi"); Gerindra Party; Golka Party; Sukarnoputri Megawati